Quality Enhancement of Physical Education in Chinese Universities from the Perspective of the Supply-side Structural Reform - Tang, Ying; Wu, Rui; Wang, Meiling (Quality in Sport, 2022)
The overall characteristics of higher education in China have been transformed from extensible development to connotative development, which is consistent with the core content of improving quality and effect in the strategy of supply-side structural reform. In response to the current dilemma of the supply-side output of physical education in Chinese universities, it calls for a balance between the demand and supply for higher physical education. In terms of exploring factors that contribute to a high-quality education system from the perspective of supply-side structural reform, the supplier, the content, the mode, and the conditions of the supply side is supposed to be optimized by improving the teaching abilities of the leading suppliers, optimizing the output of the supply content, facilitating a collaborative supply model, and expanding the online supply field. Accordingly, the coordinated and unified development of the supply and demand of physical education for college students can be promoted, to enhance the quality of physical education in Chinese universities.